Mandatory International Financial Reporting Standards 7 (IFRS 7) disclosure by listed banks in Nigeria - Zango, Adamu Garba; Kamardin, Hasnah; Ishak, Rokiah (MCSER Publishing, Rome-Italy, 2015)
The paper assesses the extent of mandatory compliance with international financial reporting standards 7 (IFRS7) by fourteen listed banks on the Nigerian stock exchange.Using a disclosure checklist of 132 mandatory disclosure requirements, the study covers a two year period of 2012 and 2013.Findings from the study reveal non-compliance with disclosure requirements. However, compliance is above average for the two years under study, an improvement is nonetheless recorded if the two years of the study are compared. Based on the result, it is recommended that monitoring and enforcement mechanisms of the Financial Reporting Council (FRC) especially on bank surveillance should be given urgent priority in view of the complex nature of banking and the need to mitigate banking crisis in Nigeria. Although Nigeria is only two years into the adoption process, banks in Nigeria can do better than what is reported in the current study.